2017
DOI: 10.4103/1995-705x.206206
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Middle Eastern patients undergoing percutaneous coronary intervention: The primary analysis of the First Jordanian PCI Registry

Abstract: Aim:This is a prospective multicenter registry designed to evaluate the incidence of adverse cardiovascular events in Middle Eastern patients undergoing percutaneous coronary interventions (PCI). The registry was also designed to determine the predictors of poor outcomes in such patients.Methods and Results:We enrolled 2426 consecutive patients who underwent PCI at 12 tertiary care centers in Jordan between January 2013 and February 2014. A case report form was used to record data prospectively at hospital adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The stent delivery success rate (>99%) was high, and the cardiac event rate at 1 year was low with low rates for cardiac death (0.6%), all MIs (0.9%) and an acceptable stent thrombosis rate (1.1%). 15 , 16 The patient population enrolled was a typical – yet unique – daily life population for this referral center with a remarkably high percentage of diabetes mellitus and other cardiovascular risk factors, and a significant number of patients presented with an acute coronary syndrome (unstable angina or an acute or recent MI). 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stent delivery success rate (>99%) was high, and the cardiac event rate at 1 year was low with low rates for cardiac death (0.6%), all MIs (0.9%) and an acceptable stent thrombosis rate (1.1%). 15 , 16 The patient population enrolled was a typical – yet unique – daily life population for this referral center with a remarkably high percentage of diabetes mellitus and other cardiovascular risk factors, and a significant number of patients presented with an acute coronary syndrome (unstable angina or an acute or recent MI). 17 …”
Section: Discussionmentioning
confidence: 99%
“…Outcomes of the first Jordanian PCI study have been reported in a separate article. 16 In total, 2,426 patients were enrolled whom underwent a PCI at 12 tertiary-care centers in Jordan. The mean age was 56±11 years, and 79% were male.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with acute coronary syndrome (ACS) are identified as those facing complicated health issues [ 5 ]. Studies conducted by Alhaddad et al and Alsheikh-Ali et al indicated ACS as one of the leading causes of death specifically in Middle East [ 6 , 7 ]. Moreover, it has been identified as considerably responsible for the occurrence of increased deaths due to cardiovascular diseases (CVDs) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery disease (CAD) is the first of ten leading causes of death worldwide including the Middle East region as noted by the World Health Organization (WHO) [ 1 ]. The classical cardiovascular risk factors that contribute to the increase in the morbidity and mortality of CAD include hypertension (HTN), diabetes mellitus (DM), dyslipidemia, and cigarette smoking [ 2 , 3 ]. It is globally agreed that lifestyle modifications and cardiovascular risk factor control would reduce the likelihood of sustaining acute coronary syndrome.…”
Section: Introductionmentioning
confidence: 99%